Morphosyntactic Errors in Students’ Written Narrative Text - Masriani Mery Rosmida Silalahi; Rakasiwi, Rani; Tampubolon, Marlina; Siahaan, Ricki Asi Erwindo (Journal of Classroom Action Research, 2024)
The objective of this study are to (1) investigate  types of errors in students’ Written Narrative Text made by students grade IX, (2) to find out the causes of errors on the students’ writing. Based on the analysis by Dulay’s theory, there are four kinds of errors: 1. Error of Omission, 2. Error of Addition, 3. Error of Misformation, 4. Error of Misorder. The dominant types of errors found in the students writings is Error of Misformation. The source of errors is analysed based on Brown’s Theory. The source of the errors are: 1) Interlingual Transfer, 2) Intralingual Transfer, 3) Context of Learning, and 4) Communication Strategy. Based on the analysis, the source of errors found are Interlingual Transfer and Intralingual Transfer. This study uses descriptive qualitative research. The subjects of this study are the students of grade IX SMK Satria Binjai. In conclusion, students make some morphosyntactic errors in their writing an d the potential cause of the errors is intralingual Transfer and Interlingual Transfer. In this case, the conclusion and the  suggestions are directed to those who would teach and learn english writing. Keywords : Error Analysis, Narrative Text, Morphosintactic